A randomised, double-blind clinical study into the effect of zinc citrate trihydrate toothpaste on oral plaque microbiome ecology and function - Suzi Elizabeth Adams; Andrew Kenneth Cawley; David Arnold; Michael John Hoptroff; Vera Slomka; Jane Reid Matheson; Robert Edward Marriott; Matthew Ronald Gemmell; Philip David Marsh (Scientific Reports)
Abstract The oral microbiome is a diverse community of microbes residing on all oral surfaces. A balanced oral microbiome is associated with good oral health, and disruption can result in imbalance associated with diseases including gingivitis and dental caries. It is important, therefore, to understand how daily use of oral hygiene products impacts the microbiome. Composition and activity of dental plaque microbiome from 115 participants was analysed after brushing with one of two toothpastes, one containing zinc citrate trihydrate and the other a control toothpaste, in a parallel design. Each participant brushed twice daily for 6-weeks, with samples collected at baseline, 2 and 6-weeks. Metataxonomic analysis demonstrated changes in bacterial communities with use of the zinc toothpaste compared to the control product at community and species level. Increases at the species level were observed for taxa from the genus Veillonella with decrease in a taxon from the genus Fusobacterium for the zinc toothpaste. Analysis of microbiome function based on predicted metagenomic and metatranscriptomic analysis show that use of the zinc toothpaste is associated with an in-vivo reduction in glycolysis, consistent with the mode of action of zinc and, increases in processes linked to gum-health (lysine biosynthesis), and to whole-body health (nitrate reduction). Our findings provide the first understanding of the beneficial modulation of microbiome composition and function by zinc-containing toothpaste in-vivo for oral care benefits.